THE MAIN SPRING OF THE MACHINE. ITINERANT JAILS IN THE PORTALES REGIME. CHILE 1830-1840. - Rivera Tobar, Francisco (Revista de Historia Social y de las Mentalidades, 2011)
This article analyzes the “presidio ambulante”  (itinerant jail) as one device of social disci - pline imposed by Chile’s conservative elites  during the period of State consolidation that  followed intra-elite struggles (1830-1840),  highlighting the role of Minister Diego  Portales. It explores critically the various  functions of the “carros jaula” (cage carts),  as well as the living conditions and resistance  mechanisms displayed by the prison inmates  vis-à-vis the authoritarian regime. The role  of this disciplinary system on the eve of the  war against the Confederacion Perú-Boliviana  is also dealt with, including its links with the  main economic processes of the early 19th  Century. In sum, this study considerers the  “presidio ambulante” as a reflection on the  elite’s views regarding the role of the popular  sectors in the making of a nation-state guided  by the principles of republicanism.
Keywords: Social History; Social Discipline; Portales Regime